Enhancing the Photocatalytic Activity of SnO2-TiO2 and ZnO-TiO2 Tandem Structures Toward Indoor Air Decontamination - Enesca, Alexandru (Frontiers in Chemistry, 2020)
ZnO-TiO2 and SnO2-TiO2 tandem structures were developed using doctor blade technique. It was found that using organic hydrophilic and hydrophobic additives allows changes in the film density and morphology with direct consequences on the photocatalytic efficiencies. ZnO-TiO2 tandem structure exhibit 74.04% photocatalytic efficiency toward acetaldehyde when hydrophilic additive is used versus 70.93% when hydrophobic additive is employed. SnO2-TiO2 presents lower photocatalytic properties (61.35 % when hydrophilic additive is used) with a constant rate reaction of 0.07771 min-1.